1999
DOI: 10.1073/pnas.96.7.3396
|View full text |Cite
|
Sign up to set email alerts
|

Long-range transport of mineral dust in the global atmosphere: Impact of African dust on the environment of the southeastern United States

Abstract: Soil dust is a major constituent of airborne particles in the global atmosphere. Dust plumes frequently cover huge areas of the earth; they are one of the most prominent and commonly visible features in satellite imagery. Dust is believed to play a role in many biogeochemical processes, but the importance of dust in these processes is not well understood because of the dearth of information about the global distribution of dust and its physical, chemical, and mineralogical properties. This paper describes some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
389
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(406 citation statements)
references
References 46 publications
13
389
0
4
Order By: Relevance
“…Barbados receives about 2.5 times more dust annually than Miami owing to higher dust concentrations and a longer dust transport season [Prospero, 1999]. However, the multiday time scale (n) of dust episodes and aerosol distributions gathered from remote sensors indicate that dust aerosol composition is similar in both Miami and Barbados [Trapp et al, 2010a], as well as the rest of the western subtropical region [Prospero, 1999]. Sea spray is another common aerosol source in both sites.…”
Section: Environmental Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Barbados receives about 2.5 times more dust annually than Miami owing to higher dust concentrations and a longer dust transport season [Prospero, 1999]. However, the multiday time scale (n) of dust episodes and aerosol distributions gathered from remote sensors indicate that dust aerosol composition is similar in both Miami and Barbados [Trapp et al, 2010a], as well as the rest of the western subtropical region [Prospero, 1999]. Sea spray is another common aerosol source in both sites.…”
Section: Environmental Settingmentioning
confidence: 99%
“…In contrast, in Miami local and regional pollution can impact our samples all year round because of land-sea breeze effects. Pollution aerosols are particularly common during the winter when wind patterns periodically shift in conjunction with coldfront passages so that Miami receives northerly air masses [Prospero, 1999;Prospero et al, 2010].…”
Section: Environmental Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…On a global scale, a region or one major ecosystem type can be a large "dust collector"; the positive or negative effects of dust collection determine whether an ecosystem is a dust source or sink and can also directly reflect the loss and accumulation of soil resources. Therefore, it has been suggested that dust plays an important role in many biogeochemical processes (Prospero, 1999;Muhs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dust storms are a significant air pollution contributor impacting urban areas as well as a health hazard for people with respiratory problems [1], [2]. Hence, timely warnings of dust storms must be initiated in populated regions for health concerns and traffic control.…”
Section: Introductionmentioning
confidence: 99%